(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This article aimed to find any relation between the eruption of the deciduous teeth and the development and growth of the child. This study included 77 children, aged between (1-2) years old all examined orally for any deciduous teeth eruption and record any delayed case, the parents of child answered 30 questions about the children’s development. The results of this study shown that there were no significant differences (P<0.05) between the teething (eruption of teeth) and the five developmental domains. Delayed teething was seen more among those with normal gross motor, and among those with delayed fine motor (statistically significant at 0.5 level). No relation between the eruption of the teeth and the development of the child and the teething time might be affected by local causes more than the systemic cause; these results need more researches and studies to prove these facts.